Do cay and cayMS predict stock and housing returns? Evidence from a nonparametric causality test - Balcilar, Mehmet; Gupta, Rangan; Sousa, Ricardo M.; Wohar, Mark E. (Elsevier, 2017)
We use a nonparametric causality-in-quantiles test to compare the predictive ability of the consumption-wealth ratio (cay) and the Markov Switching version (cay(MS)) for excess and real stock and housing returns and their volatility. Our results reveal strong evidence of nonlinearity and regime changes in the relationship between asset returns and cay or Cay(MS), which corroborates the relevance of this econometric framework. Moreover, both cay or Cay(MS) are found to predict only excess stock returns over its entire conditional distribution, with the latter being a strong predictor only at certain quantiles. As for the housing market, these two consumption-wealth ratios only predict the volatility of real housing returns, with cay(MS) outperforming cay over the majority of the conditional distribution.
Keywords: Stock returns; Housing returns; Causality-in-quantiles test; Nonparametric